Amending section 25 of the South African Constitution to allow for expropriation of land without compensation: some theoretical considerations of the social-obligation norm of ownership. Issue 2 (3rd April 2019) - Sibanda, Nkanyiso
Abstract: The passage of the motion to expropriate land without compensation in the National Assembly on the 27 February 2018 sparked numerous discussions on how this would be legally implemented. On 5 December 2018, the National Council of Provinces agreed that s 25 of the Constitution of the Republic of South Africa, 1996 should be amended to provide for the expropriation of land without compensation. Of course, a key question that needs to be answered relates to how this envisaged amendment will be made, its nature as well as its specific provisions. This paper suggests that the social-obligation norm theory of ownership should be the underlying guide for amending s 25 to allow for expropriation of land without compensation. I argue that because land is a unique form of property from which we derive our livelihood, whatever constitutional amendments that might be adopted to allow for its expropriation without compensation should ensure that it is ultimately utilised actively, productively and sustainably. This can be achieved through the inculcation of the social-obligation norm of ownership into the property clause. The classical idea that ownership is a sacrosanct and inviolable real relationship cannot be accepted rigidly when it comes to land. Even the ius abutendi, a key entitlement of ownership, which allows owners to do as they please with their property, never envisaged wasteful neglect of a resource such as land.